Does it pay to work from home? Examining the factors influencing working from home in the Greater Dublin Area - CAULFIELD, BRIAN (My University, 2015)
Encouraging working from home or telecommuting has long been seen as a means to encourage sustainable mobility. With i ncrease coverage of high - speed I nternet access and escalating transport costs, telecommuting has become more attractive than ever. This paper seeks to explore the factors that encourage telecommuting in the Greater Dublin Area (GDA) in Ireland. The research pre sented in this paper considers how factors such as public transport access, deprivation, industrial grouping, car ownership, household st ructure and residential density, impact upon the decision to work from home. The paper also seeks to determine the cos t savings in terms of travel time saved that those telecommuting enjoy on an annual basis. The find ings of this study show a substantial travel time and cost of travel time saving in the GDA. The findings also suggest areas several factors such as broadb and Internet coverage, public transport availability and occupation all impact upon the propensity to work from home.
PUBLISHED
Keywords: telecommuting; Smart & Sustainable Planet